The Whip Law, Implementing Shari’a Formalization at Local Community: The Case Of Padang Village In Bulukumba, South Sulawesi - Kadir Ahmad, Abd. (International Journal of Engineering and Technology, 2018)
Indonesia experienced a major change after the reformation. Various new religious organizations emerged followed by the movement of formalization and politicization of religion. The regions seem to compete in issuing Shari'a regulations. Even the formalization of the religion is not only applicable at the district level but also in certain areas have reached the village level in the form of Muslim Villages. One of the Muslim Villages in South Sulawesi is the Muslim Village of Padang in Bulukumba District. This village makes a Village Regulation on the Law of Whip. The aim of the research is to understand the existence, sustainability and the supporting factors of the caning law. The research finds the implementation of Whip Law as one of the instruments supporting the implementation of Islamic Shari’a  in Padang Village only runs at the beginning of its enactment. Some of the factors causing the failure of  the step are changes in leadership and priority program differences by local leaders, political competition at the village government level and lack of cultural support from the local community.